Algorithmic Game Theory : 15th international symposium, SAGT 2022, Colchester, UK, September 12-15,2022 proceedings (Cham, Switzerland: Springer, 2022)
This book constitutes the proceedings of the 15th International Symposium on Algorithmic Game Theory, SAGT 2022, which took place in Colchester, UK, in September 2022. The 31 full papers included in this book were carefully reviewed and selected from 83 submissions. They were organized in topical sections as follows: Auctions, markets and mechanism design; computational aspects in games; congestion and network creation games; data sharing and learning; social choice and stable matchings.
Keywords: Data Modeling & Design; Computer Simulation; General, Information Technology